Macroscopic and microscopic insights into the co-aggregation behavior of mixed fish gelatins with different melting points - Lester C. Geonzon; Kaede Takatsuno; Mei Murakami; Sanjida Humayun; Koichi Mayumi; Rando Tuvikene; Yoko Nitta; Motoyoshi Kobayashi; Shingo Matsukawa (Food Hydrocolloids, 2026)

Optimizing Analog Identification and Evaluation in the OECD QSAR Toolbox to Enable Robust Read-Across - E. Byrd; C. Albertson; P. Kern; L. Reinsalu; J. Rose; G. Yan; X. Zhang; C. Lester (Regulatory Toxicology and Pharmacology, 2026)

Measuring changes in environmental radiological background from construction of an advanced nuclear reactor testing facility - Jim Drachenberg; James E. Johnstone; Gage McClaine; Rusty S. Towell; Jared Barker; Neddy Chepkoech; Dale Cox; John C. Dalton; T.L. Head; Timothy J. Kennedy; Kim L. Pamplin; Jackson Shoultz; et al. (Journal of Environmental Radioactivity, 2026)

Multiscale structural and mechanical characterization of acid milk gels with low-concentration fish gelatin during gelation and cold storage - Izumi Sone; Kaede Takatsuno; Lester C. Geonzon; Hazuku Takagi; Chuhuan Hu; Catherine Taylor Nordgård; Koichi Mayumi; Shingo Matsukawa (Food Hydrocolloids, 2026)

Racial and ethnic disparities in environmental chemical exposures and hypertensive disorders of pregnancy: The ECHO-wide cohort study - Hongxiu Liu; Amii M. Kress; Emma X. Yu; Xuejuan Ning; Akhgar Ghassabian; Linda G. Kahn; Shilpi Mehta-Lee; Sara Brubaker; Akram Alshawabkeh; John Meeker; Carlos A. Camargo; Shakira F. Suglia; et al. (Environmental Pollution, 2026)

Perinatal exposure to delta-9-tetrahydrocannabinol (THC) alters goal-directed behavior and dopamine functioning in wistar rats - Monica S. Carbajal; Rebecca C. Crenshaw; Victoria E. Williams; Laura G. Billings; Chelsea M. Dixon; Deranda B. Lester; Helen J. K. Sable (Psychopharmacology, 2026)
Rationale Cannabis use during 2021pregnancy is common as many pregnant women consider cannabis as a safe way to alleviate symptoms associated with pregnancy because it is “natural”. However, clinical evidence links perinatal cannabis exposure to externalizing behavior in offspring. In preclinical research, most studies focus on exposure to the psychoactive constituent of cannabis, delta-9-tetrahydrocannabinol (THC). THC is lipophilic, allowing it to cross the placental barrier and be secreted in maternal milk, thereby exposing the fetus/neonate. Objective We used operant procedures to measure motivation and impulsivity in adult offspring perinatally exposed to THC. Methods Dams were orally exposed to 0 or 5 mg/kg/day THC daily from 14 days prior to breeding to postnatal day (PND) 14. Differential reinforcement of high rates (DRH) and differential reinforcement of low rates (DRL) of responding tasks were used to examine motivation and impulsive action. We also measured dopamine (DA) functioning in the medial prefrontal cortex (mPFC) and nucleus accumbens (NAc) via in vivo fixed potential amperometry in littermates of rats that completed behavioral testing. Results Perinatal THC exposure had minimal effects on impulsive action measures during DRL 15s. Rather, perinatal THC exposure decreased DRL 15s burst responses and completed trials in both sexes, and reinforcers earned in THC-exposed males. Decreased lever presses during DRH were observed in both sexes perinatally exposed to THC, as well as fewer reinforcers in THC-exposed males. THC exposure did not alter baseline DA release in the NAc or mPFC, but did attenuate the dopaminergic response to cocaine in the NAc. Conclusions These results suggest perinatal exposure to THC can decrease motivation to work for reinforcers during high-effort tasks, that this effect may be more pronounced in males, and that the “amotivational state” resulting from perinatal THC exposure may be due to reinforcer devaluation. Keywords : oral THC, developmental neurotoxicology, amotivational syndrome, mesocorticolimbic dopamine.

FracFeed : Global database of the fraction of feeding predators - Mark Novak; Paige Foust; Shannon Hennessey; Brian P. Tanis; Kyle E. Coblentz; Christopher Wolf; Leah M. Segui; Jeremy S. Henderson; Kurt E. Ingeman; Landon P. Falke; Tamara J. Layden; Daniel J. Gradison; et al. (Ecology, 2026)
The proportion of individuals that are found to have empty stomachs during a survey of a predator population's diet has been used as an indicator of the average individual's state of energy balance and of the degree to which its feeding rate (i.e., its functional response) is saturated with respect to prey availability. As such, the proportion of empty stomachs provides insights into the effects of prey on predators and vice versa, although it is typically unreported in deference to descriptions of the contents of the non‐empty stomachs. The FracFeed database is an ongoing compilation of the proportions of empty and non‐empty stomachs (for gut content surveys) and of feeding and not feeding individuals (for direct observation surveys) reported in publications of predator diet surveys. FracFeed contains data from 4920 diet surveys on 1507 taxa (>4.3 million individuals) spanning cnidarians, ctenophores, chaetognaths, birds, annelids, amphibians, arthropods, mammals, mollusks, reptiles, echinoderms, and fishes that were surveyed in terrestrial, marine, and freshwater ecosystems across the globe over more than 135 years (1887–2023). For most surveys, covariate data include information on the spatial and temporal extent of the diet survey, its central geographical coordinates, the method by which the survey was performed (lethal gut contents, lavage, or direct observation), as well as each predator's standardized taxonomic name and identifier in the Open Tree of Life, its body mass (compiled mostly from independent compilations and additional publications), and its apparent diet's taxonomic richness and resolution. We appeal to more researchers who perform diet surveys to report on the number of empty stomachs they find and encourage additional contributions to the database—particularly from underrepresented geographic regions (e.g., North and Central Asia, North and Central Africa)—to help grow its scope and utility. The database is provided under a CC‐BY‐NC‐S4 4.0 license. Users are requested to cite this data paper when using the data.

Gelation mechanism and network structure of mixed cold-water fish gelatin and pork skin gelatin elaborated at the molecular level - Lester C. Geonzon; Yumika Hayano; Hazuku Takagi; Kaede Takatsuno; Yoko Nitta; Koichi Mayumi; Shingo Matsukawa (Food Hydrocolloids, 2025)

Streptococcus dysgalactiae From Farm‐Raised Channel Catfish in Mississippi, USA, With Notes on Fish‐Associated Group C S. dysgalactiae - Sujita Balami; Lester H. Khoo; Caitlin E. Older; Geoffrey C. Waldbieser; Alvin C. Camus; Taylor I. Heckman; Cynthia C. Ware; Bradley M. Richardson; John P. Hawke; Adrián López‐Porras; Esteban Soto; Craig A. Shoemaker; et al. (Journal of Fish Diseases, 2025)
Lancefield serological group C Streptococcus dysgalactiae (GCSD) is an emerging cause of fish disease worldwide, largely associated with mariculture in Asia. In the United States (US), GCSD had been a pathogen of minimal concern for fish, but recent cases indicate a putative emergence in wild and cultured freshwater fish populations in the Americas. The current study discusses three novel cases of GCSD‐associated streptococcosis in US farm‐raised channel catfish ( Ictalurus punctatus ) occurring in Mississippi, US, in 2022 and 2023. Infected fish presented with pendulous abdomens, red swollen vents, and petechiae on the mouth, fins and ventral lateral abdomen. Clinical isolates were cultured from the kidney and brain and initially confirmed as GCSD by 16S rRNA gene sequencing, followed by phylogenetic analyses using the superoxide dismutase gene ( sod A), 16S/23S internal transcribed spacer region and nine genes within a multilocus sequence analysis scheme for piscine pathogenic Streptococcus . Catfish GCSD were highly homologous to fish strains from published reports from Asia and South America, forming a discrete phylogenetic clade, separate from human and other terrestrial animal isolates. Pairwise genomic comparisons suggest this fish‐associated group does not belong to any currently recognised subspecies and may represent a unique subtype. The broadening host and geographic range of GCSD, coupled with the evidence of a discrete aquatic lineage and recent reports from freshwater fishes in the southeastern US, suggest GCSD is a potential emergent threat to catfish aquaculture in the US.

Precision forestry in actively managed loblolly pine plantations: Leaf area index response one growing season following a variable-rate fertilization - Chris W. Cohrs; Al Lyons; Timothy J. Albaugh; David R. Carter; Otávio C. Campoe; Rafael A. Rubilar; Matthew Sumnall; Andrew Trlica; Mark V. Corrao; Simerjeet Virk; Rex Lester; Rachel L. Cook (Forest Ecology and Management, 2025)

Love bites? Pre-copulatory behaviours of whale sharks (Rhincodon typus) at Ningaloo Reef, Western Australia - Christine Barry; Emily Lester; Micheal P. Doane; Luciana C. Ferreira; Michele Thums; Adrian C. Gleiss; Mark G. Meekan (Frontiers in Marine Science, 2025)
Very little is known about the reproductive behaviours of whale sharks ( Rhincodon typus ). Here, we describe field observations of courtship behaviour by a whale shark at Ningaloo Reef, Western Australia. We witnessed and recorded following and biting behaviours by a sexually mature male of a smaller female. Following and biting are common events during courtship and copulation of other species of elasmobranchs. Our observations are consistent with earlier reports of courting behaviours in whale sharks provided by fishers, the pilot of a light plane and observations of courtship by a sexually mature male towards females held in aquaria.

Elucidating the rheological and thermal properties of mixed fish and pork skin gelatin gels: Effects of cooling conditions and incubation times - Lester C. Geonzon; Hazuku Takagi; Yumika Hayano; Kurt Ingar Draget; Catherine Taylor Nordgård; Shingo Matsukawa (Food Hydrocolloids, 2024)

First records of the Southeast Asian-Australasian lepidopteran egg parasitoid, Telenomus remus Nixon [Hymenoptera: Scelionidae] in Việt Nam and Lao PDR - Hang Thi Dao; George A. C. Beattie; Lam Van Pham; Viengvilay Vorlachith; Chanthason Vongtharone; Bouasa Xaisongkham; Kitan Sitthisay; Paul Holford; Lester W. Burgess (International Journal of Tropical Insect Science, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Recent deep-sea nematodes and agglutinated foraminifera select specific grains and bioclasts from their environments: Ecological implications - Sunil K. Das; Raj K. Singh; Mariem Saavedra-Pellitero; Julia Gottschalk; Carlos A. Alvarez Zarikian; Lester Lembke-Jene; Frank Lamy; Gisela Winckler; Jennifer L. Middleton; Helge W. Arz; Chandranath Basak; Anieke Brombacher; et al. (Marine Micropaleontology, 2024)

Late Miocene to Early Pliocene paleoceanographic evolution of the Central South Pacific: A deep-sea benthic foraminiferal perspective - Sunil K. Das; N. Mahanta; B. Sahoo; Raj K. Singh; Carlos A. Alvarez Zarikian; Manish Tiwari; Nishant Vats; Nihal; Frank Lamy; Gisela Winckler; Jennifer L. Middleton; Helge W. Arz; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Identifying priority sites for whale shark ship collision management globally - Freya C. Womersley; Christoph A. Rohner; Kátya Abrantes; Pedro Afonso; Shin Arunrugstichai; Steffen S. Bach; Shir Bar; Adi Barash; Peter Barnes; Adam Barnett; Ginevra Boldrocchi; Noemie Buffat; et al. (Science of The Total Environment, 2024)

Associations between neighborhood characteristics and child well-being before and during the COVID-19 pandemic: A repeated cross-sectional study in the Environmental influences on Child Health Outcomes (ECHO) program - Xueying Zhang; Courtney K. Blackwell; Janet Moore; Shelley H. Liu; Chang Liu; Christopher B. Forrest; Jody Ganiban; Annemarie Stroustrup; Judy L. Aschner; Leonardo Trasande; Sean C.L. Deoni; Amy J. Elliott; et al. (Environmental Research, 2024)

Understanding the rheological properties from linear to nonlinear regimes and spatiotemporal structure of mixed kappa and reduced molecular weight lambda carrageenan gels - Lester C. Geonzon; Takato Enoki; Sanjida Humayun; Rando Tuvikene; Shingo Matsukawa; Koichi Mayumi (Food Hydrocolloids, 2024)

The effects of stem bromelain on the gelation behavior of kappa carrageenan under linear and nonlinear rheological regimes - Wilfred V. Rios; Lester C. Geonzon; Arlyn M. Roque; Ma Roxan B. Abiquibil; Mary Diane A. Pilapil; Mark Adones P. Lingaro; Hyacinth N. Suarez; Raymund Lee Antonio C. Sarmiento; Shingo Matsukawa; Rommel G. Bacabac (Food Hydrocolloids, 2024)

The combined effects of treated sewage discharge and land use on rivers - Dania Albini; Lauren Lester; Philip Sanders; Jocelyne Hughes; Michelle C. Jackson (Global Change Biology, 2023)
Freshwater ecosystems are increasingly threatened by multiple anthropogenic stressors. Release of treated sewage effluent and pollution from agricultural or urban sources can independently reduce water quality with implications for ecological communities. However, our knowledge of the combined effects of these stressors is limited. We performed a field study to quantify the combined effect of treated sewage discharge and land use on nutrient concentrations, sewage fungus presence and communities of macroinvertebrates and benthic algae. Over three seasons in four rivers we found that a model which included an interaction between sewage pollution and time of the year (i.e. months) was the best predictor of nutrient concentrations and the abundance of algae and sewage fungus. Both macroinvertebrate and algae communities shifted downstream of sewage input. Specifically, more tolerant groups, such as cyanobacteria and oligochaetes, were more abundant. The EPT (Ephemeroptera, Plecoptera and Tricoptera) water quality score was best explained by an interaction between month and agriculture in the surrounding landscape. Overall, our results show that sewage discharge has a significant impact on water quality and benthic riverine communities, regardless of the surrounding land uses. Agricultural inputs, however, could be more important than treated sewage discharge in reducing the abundance of sensitive invertebrate taxa. We need both improvements to wastewater treatment processes and reductions in agricultural pollution to reduce threats to vulnerable freshwater communities.

Effects of nanofertilizer and nano-plant hormone on soil chemical properties and microbial community in two different soil types - John Lester Viscara PIDE; Nolissa Delmo ORGANO; Andre Freire CRUZ; Lilia M. FERNANDO; Lucille C. VILLEGAS; Evelyn F. DELFIN; Michelle Ann Magat CALUBAQUIB; Roselle Estera MADAYAG; Erlinda S. PATERNO (Pedosphere, 2023)

Change of network structure in agarose solution during gelation studied by multiple particle tracking and NMR measurements - Hwabin Jung; Lester C. Geonzon; Won Byong Yoon; Shingo Matsukawa (Food Hydrocolloids, 2023)

Microrheological properties and local structure of ι-carrageenan gels probed by using optical tweezers - Lester C. Geonzon; Motoyoshi Kobayashi; Manlio Tassieri; Rommel G. Bacabac; Yasuhisa Adachi; Shingo Matsukawa (Food Hydrocolloids, 2023)

Diversity in marine protected area regulations: Protection approaches for locally appropriate marine management - Dominic A. Andradi-Brown; Laura Veverka; Amkieltiela; Nicole L. Crane; Estradivari; Helen E. Fox; David Gill; Jordan Goetze; Charlotte Gough; Nils C. Krueck; Sarah E. Lester; Shauna L. Mahajan; et al. (Frontiers in Marine Science, 2023)
Globally, marine protected area (MPA) objectives have increasingly shifted from a primary focus on maintaining ecosystems through prohibiting extractive activities, to more equitable approaches that address the needs of both people and nature. This has led to MPAs with a diverse array of fisheries restrictions and recent debate on the type of restrictions that contribute to achieving biodiversity goals. Here we use a global dataset of 172 MPAs (representing 31 nations) alongside nine detailed case study MPAs (from Australia, Belize, Cambodia, Federated States of Micronesia, Fiji, Indonesia, Madagascar, Solomon Islands, and United States of America), including partially protected areas that allow regulated fishing, to illustrate the many diverse pathways that some MPAs have adopted to protect biodiversity and safeguard the rights and well-being of resource-dependent coastal communities. We group MPAs based on their restrictions and explore four key insights emerging from these groupings using our nine case studies: (i) MPAs use highly diverse approaches to regulate fisheries; (ii) partially protected areas can address gaps in regional fisheries management; (iii) devolving resource management rights to communities influences the chosen fisheries restrictions; and (iv) state-governed MPAs can use highly tailored fisheries restrictions to increase equity in access. We find that partially protected MPAs can offer effective and equitable pathways for biodiversity conservation if tailored to local context. Rather than focusing primarily on fully protected areas for achieving new global MPA targets, we recommend countries use a blend of locally-appropriate protection levels – from fully protected areas to partially protected MPAs to achieve positive biodiversity outcomes.

Modified future diurnal variability of the global surface ocean CO 2 system - Lester Kwiatkowski; Olivier Torres; Olivier Aumont; James C. Orr (Global Change Biology, 2023)
Our understanding of how increasing atmospheric CO 2 and climate change influences the marine CO 2 system and in turn ecosystems has increasingly focused on perturbations to carbonate chemistry variability. This variability can affect ocean‐climate feedbacks and has been shown to influence marine ecosystems. The seasonal variability of the ocean CO 2 system has already changed, with enhanced seasonal variations in the surface ocean p CO 2 over recent decades and further amplification projected by models over the 21st century. Mesocosm studies and CO 2 vent sites indicate that diurnal variability of the CO 2 system, the amplitude of which in extreme events can exceed that of mean seasonal variability, is also likely to be altered by climate change. Here, we modified a global ocean biogeochemical model to resolve physically and biologically driven diurnal variability of the ocean CO 2 system. Forcing the model with 3‐h atmospheric outputs derived from an Earth system model, we explore how surface ocean diurnal variability responds to historical changes and project how it changes under two contrasting 21st‐century emission scenarios. Compared to preindustrial values, the global mean diurnal amplitude of p CO 2 increases by 4.8 μatm (+226%) in the high‐emission scenario but only 1.2 μatm (+55%) in the high‐mitigation scenario. The probability of extreme diurnal amplitudes of p CO 2 and [H + ] is also affected, with 30‐ to 60‐fold increases relative to the preindustrial under high 21st‐century emissions. The main driver of heightened p CO 2 diurnal variability is the enhanced sensitivity of p CO 2 to changes in temperature as the ocean absorbs atmospheric CO 2 . Our projections suggest that organisms in the future ocean will be exposed to enhanced diurnal variability in p CO 2 and [H + ], with likely increases in the associated metabolic cost that such variability imposes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

A Scientific Synthesis of Marine Protected Areas in the United States: Status and Recommendations - Jenna Sullivan-Stack; Octavio Aburto-Oropeza; Cassandra M. Brooks; Reniel B. Cabral; Jennifer E. Caselle; Francis Chan; J. Emmett Duffy; Daniel C. Dunn; Alan M. Friedlander; Heather K. Fulton-Bennett; Steven D. Gaines; Leah R. Gerber; et al. (Frontiers in Marine Science, 2022)
Marine protected areas (MPAs) are a key tool for achieving goals for biodiversity conservation and human well-being, including improving climate resilience and equitable access to nature. At a national level, they are central components in the U.S. commitment to conserve at least 30% of U.S. waters by 2030. By definition, the primary goal of an MPA is the long-term conservation of nature; however, not all MPAs provide the same ecological and social benefits. A U.S. system of MPAs that is equitable, well-managed, representative and connected, and includes areas at a level of protection that can deliver desired outcomes is best positioned to support national goals. We used a new MPA framework, The MPA Guide, to assess the level of protection and stage of establishment of the 50 largest U.S. MPAs, which make up 99.7% of the total U.S. MPA area (3.19 million km 2 ). Over 96% of this area, including 99% of that which is fully or highly protected against extractive or destructive human activities, is in the central Pacific ocean. Total MPA area in other regions is sparse – only 1.9% of the U.S. ocean excluding the central Pacific is protected in any kind of MPA (120,976 km 2 ). Over three quarters of the non-central Pacific MPA area is lightly or minimally protected against extractive or destructive human activities. These results highlight an urgent need to improve the quality, quantity, and representativeness of MPA protection in U.S. waters to bring benefits to human and marine communities. We identify and review the state of the science, including focal areas for achieving desired MPA outcomes and lessons learned from places where sound ecological and social design principles come together in MPAs that are set up to achieve national goals for equity, climate resilience, and biodiversity conservation. We recommend key opportunities for action specific to the U.S. context, including increasing funding, research, equity, and protection level for new and existing U.S. MPAs.

New data on Henneguya postexilis Minchew, 1977, a parasite of channel catfish Ictalurus punctatus, with notes on resolution of molecular markers for myxozoan phylogeny - Ethan T. Woodyard; Thomas G. Rosser; Justin M. Stilwell; Alvin C. Camus; Lester H. Khoo; Geoffrey Waldbieser; W. Walter Lorenz; Matt. J. Griffin (Systematic Parasitology, 2022)

How do fisher responses to macroalgal overgrowth influence the resilience of coral reefs? - Andrew Rassweiler; Scott D. Miller; Sally J. Holbrook; Matthew Lauer; Mark A. Strother; Sarah E. Lester; Thomas C. Adam; Jean Wencélius; Russell J. Schmitt (Limnology and Oceanography, 2022)
Many coral reefs have shifted from coral‐ to macroalgae‐dominated community states, heightening the need to understand resilience of coral communities. Fishing on herbivores often reduces resilience of the coral state, as lower herbivory fosters macroalgal establishment. Despite the acknowledged importance of fishing, relatively little attention has been paid to how fishers change their behavior as macroalgae overgrow reefs, or how the resulting dynamic feedbacks might affect resilience. We address these questions in Moorea, French Polynesia, where local fishers target herbivorous fishes and where shifts to algal dominance have occurred on some lagoon reefs. We quantified fisher preferences for reef habitats where they target various taxa. For the two most ecologically important taxa of herbivores targeted in the fishery, parrotfish (Scaridae) and unicornfish ( Naso ), fishers preferred to harvest from locations with less macroalgae. We incorporated these habitat preferences into a spatially explicit social–ecological model of reef dynamics to explore consequences of changes in fishing behavior for resilience of the coral state, particularly following disturbance. Fishing that targets low‐macroalgae locations typically generates resilience by facilitating local recovery of herbivores and thus of coral in the less‐targeted macroalgae‐dominated patches. However, the resulting movement of fishers across the seascape can sometimes create fragility; if coral loss is widespread, avoidance of macroalgae concentrates fishing in patches having the highest coral cover, resulting in loss of coral via reduced herbivory. Our results emphasize that resilience and coral‐macroalgae regime shifts cannot be understood without considering humans as a dynamic part of the system.

Predicting Fluid Flow Regime, Permeability, and Diffusivity in Mudrocks from Multiscale Pore Characterisation - Amirsaman Rezaeyan; Vitaliy Pipich; Jingsheng Ma; Leon Leu; Timo Seemann; Gernot Rother; Lester C. Barnsley; Andreas Busch (Transport in Porous Media, 2022)
In geoenergy applications, mudrocks prevent fluids to leak from temporary (H 2 , CH 4 ) or permanent (CO 2 , radioactive waste) storage/disposal sites and serve as a source and reservoir for unconventional oil and gas. Understanding transport properties integrated with dominant fluid flow mechanisms in mudrocks is essential to better predict the performance of mudrocks within these applications. In this study, small-angle neutron scattering (SANS) experiments were conducted on 71 samples from 13 different sets of mudrocks across the globe to capture the pore structure of nearly the full pore size spectrum (2 nm–5 μm). We develop fractal models to predict transport properties (permeability and diffusivity) based on the SANS-derived pore size distributions. The results indicate that transport phenomena in mudrocks are intrinsically pore size-dependent. Depending on hydrostatic pore pressures, transition flow develops in micropores, slip flow in meso- and macropores, and continuum flow in larger macropores. Fluid flow regimes progress towards larger pore sizes during reservoir depletion or smaller pore sizes during fluid storage, so when pressure is decreased or increased, respectively. Capturing the heterogeneity of mudrocks by considering fractal dimension and tortuosity fractal dimension for defined pore size ranges, fractal models integrate apparent permeability with slip flow, Darcy permeability with continuum flow, and gas diffusivity with diffusion flow in the matrix. This new model of pore size-dependent transport and integrated transport properties using fractal models yields a systematic approach that can also inform multiscale multi-physics models to better understand fluid flow and transport phenomena in mudrocks on the reservoir and basin scale.

Estimating different order polynomial logarithmic environmental Kuznets curves - Fakhri J. Hasanov; Lester C. Hunt; Jeyhun I. Mikayilov (Environmental Science and Pollution Research, 2021)
This paper contributes to the environmental literature by (i) demonstrating that the estimated coefficients and the statistical significance of the non-leading terms in quadratic, cubic, and quartic logarithmic environmental Kuznets curve (EKC) specifications are arbitrary and should therefore not be used to choose the preferred specification and (ii) detailing a proposed general-to-specific type methodology for choosing the appropriate specifications when attempting to estimate higher-order polynomials such as cubic and quartic logarithmic EKC relationships. Testing for the existence and shape of the well-known EKC phenomenon is a hot topic in the environmental economics literature. The conventional approach widely employs quadratic and cubic specifications and more recently also the quartic specification, where the variables are in logarithmic form. However, it is important that researchers understand whether the estimated EKC coefficients, turning points, and elasticities are statistically acceptable, economically interpretable, and comparable. In addition, it is vital that researchers have a clear structured non-arbitrary methodology for determining the preferred specification and hence shape of the estimated EKC. We therefore show mathematically and empirically the arbitrary nature of estimated non-leading coefficients in quadratic, cubic, and quartic logarithmic EKC specifications, being dependent upon the units of measurement chosen for the independent variables (e.g. dependent upon a rescaling of the variables such as moving from $m to $bn). Consequently, the practice followed in many previously papers, whereby the estimates of the non-leading terms are used in the decision to choose the preferred specification of an estimated EKC relationship, is incorrect and should not be followed since it potentially could lead to misleading conclusions. Instead, it should be based upon the sign and statistical significance of the estimated coefficients of the leading terms, the location of turning point(s), and the sign and statistical significance of the estimated elasticities. Furthermore, we suggest that researchers should follow a proposed general-to-specific type methodology for choosing the appropriate order of polynomials when attempting to estimate higher-order polynomial logarithmic EKCs.

Study on salinity penetration process into fish meat by simulation and MRI - Lester C. Geonzon; Hannah A. Yuson; Kigen Takahashi; Shingo Matsukawa (Fisheries Science, 2021)

Asthma and high-intensity interval training have no effect on clustered cardiometabolic risk or arterial stiffness in adolescents - M. A. McNarry; L. Lester; E. A. Ellins; J. P. Halcox; G. Davies; C. O. N. Winn; K. A. Mackintosh (European Journal of Applied Physiology, 2021)
Purpose Cardiometabolic risk, including arterial stiffness, is increasing in youth. Those with asthma are suggested to be particularly at risk of cardiovascular disease. Efficient and effective strategies are required to prevent the atherosclerotic process in youth. The purpose of this study was to investigate the effect of 6 months high-intensity interval training (HIIT) on cardiometabolic risk in youth with and without asthma. Methods 65 adolescents (31 mild asthma; 34 non-asthma) were recruited, 32 (16 asthma) of whom were randomly allocated to receive HIIT three times per week for 6 months. At baseline, mid-intervention, post-intervention and at a 3-month follow-up, anthropometric, metabolic and vascular determinants of cardiometabolic risk were assessed. Following principal component analysis (PCA), linear mixed models were used to assess the influence of asthma, HIIT and their interaction. Results Seven factors were identified which explained 88% of the common variance shared among the parameters. Those with asthma demonstrated lower arterial stiffness factor scores mid-intervention ( P = 0.047) and lower cholesterol factor scores post-intervention ( P = 0.022) but there was no effect of the intervention, or interaction effects, on any PCA-identified factor, at any time-point. HIIT was associated with a lower low-density lipoprotein and diastolic blood pressure at mid-intervention. Discussion Neither arterial stiffness nor clustered cardiometabolic risk are influenced by HIIT in adolescents with or without asthma, despite important changes in blood lipid and pressure profiles. Blood pressure, augmentation and pulse wave velocity should be considered physiologically distinct constructs and as potential markers of cardiovascular health.

Asymptotic Growth of Whale Sharks Suggests Sex-Specific Life-History Strategies - Mark G. Meekan; Brett M. Taylor; Emily Lester; Luciana C. Ferreira; Ana M. M. Sequeira; Alistair D. M. Dove; Matthew J. Birt; Alex Aspinall; Kim Brooks; Michele Thums (Frontiers in Marine Science, 2020)

Tracking Improvement in Simulated Marine Biogeochemistry Between CMIP5 and CMIP6 - Roland Séférian; Sarah Berthet; Andrew Yool; Julien Palmiéri; Laurent Bopp; Alessandro Tagliabue; Lester Kwiatkowski; Olivier Aumont; James Christian; John Dunne; Marion Gehlen; Tatiana Ilyina; et al. (Current Climate Change Reports, 2020)
Purpose of Review The changes or updates in ocean biogeochemistry component have been mapped between CMIP5 and CMIP6 model versions, and an assessment made of how far these have led to improvements in the simulated mean state of marine biogeochemical models within the current generation of Earth system models (ESMs). Recent Findings The representation of marine biogeochemistry has progressed within the current generation of Earth system models. However, it remains difficult to identify which model updates are responsible for a given improvement. In addition, the full potential of marine biogeochemistry in terms of Earth system interactions and climate feedback remains poorly examined in the current generation of Earth system models. Summary Increasing availability of ocean biogeochemical data, as well as an improved understanding of the underlying processes, allows advances in the marine biogeochemical components of the current generation of ESMs. The present study scrutinizes the extent to which marine biogeochemistry components of ESMs have progressed between the 5th and the 6th phases of the Coupled Model Intercomparison Project (CMIP).

Lack of genetic structuring, low effective population sizes and major bottlenecks characterise common and German wasps in New Zealand - Julia M. Schmack; Evan C. Brenton-Rule; Ruan Veldtman; Tom Wenseleers; Jacqueline R. Beggs; Philip J. Lester; Mariana Bulgarella (Biological Invasions, 2019)

Practical Approaches and Advances in Spatial Tools to Achieve Multi-Objective Marine Spatial Planning - Amanda T. Lombard; Natalie C. Ban; Joanna L. Smith; Sarah E. Lester; Kerry J. Sink; Spencer A. Wood; Aerin L. Jacob; Zacharoula Kyriazi; Richard Tingey; Helena E. Sims (Frontiers in Marine Science, 2019)

The origins of global invasions of the German wasp (Vespula germanica) and its infection with four honey bee viruses - Evan C. Brenton-Rule; Jana Dobelmann; James W. Baty; Robert L. Brown; Libor Dvorak; Julien Grangier; Maité Masciocchi; Chris McGrannachan; Chris R. Shortall; Julia Schmack; Carolien van Zyl; Ruan Veldtman; et al. (Biological Invasions, 2018)

Temperature threshold models for benthic macroinvertebrates in Idaho wadeable streams and neighboring ecoregions - David C. Richards; Gary Lester; John Pfeiffer; Jason Pappani (Environmental Monitoring and Assessment, 2018)

Complex movement patterns by foraging loggerhead sea turtles outside the breeding season identified using Argos‐linked Fastloc‐Global Positioning System - Antoine M. Dujon; Gail Schofield; Rebecca E. Lester; Kostas Papafitsoros; Graeme C. Hays (Marine Ecology, 2018)
We used Argos‐linked Fastloc‐Global Positioning System (Argos‐linked Fastloc‐GPS) satellite tags to investigate how loggerhead sea turtles use neritic foraging habitats at multiple scales. Out of 24 turtles, six individuals used more than one foraging site, with all sites being separated by >25 km. These six individuals used up to four sites, remaining at each site for a mean of 150 days and returning to the same site a minimum of 52 days later. The other 18 turtles remained in a single site. The area within sites was not used uniformly, with 15 out of 24 turtles exhibiting complex movement patterns within and amongst up to five focal patches, which were typically 0.1–5.0 km apart within a single site. Movements between sites and patches might sometimes have reflected overwintering behaviour; however, similar movement patterns occurred at multiple times of the year, suggesting other factors were also involved. Use of multiple sites and patches might be driven by differences in resource availability, such as food and/or night‐time refuges, competition, or exploratory movement to investigate or locate alternative patches. We confirmed competition via direct visual observations of aggressive interactions between individuals at one foraging patch. Our results illustrate the importance of standardizing data to the same number of locations per day and night to accurately delineate key areas used by turtles or for evidence‐based marine protected area planning.

Fastloc-GPS reveals daytime departure and arrival during long-distance migration and the use of different resting strategies in sea turtles - Antoine M. Dujon; Gail Schofield; Rebecca E. Lester; Nicole Esteban; Graeme C. Hays (Marine Biology, 2017)

Equine Pulmonary Cryptococcosis: A Comparative Literature Review and Evaluation of Fluconazole Monotherapy - C. J. Secombe; G. D. Lester; M. B. Krockenberger (Mycopathologia, 2017)

Four putative entomopathogenic fungi of armoured scale insects on Citrus in Australia - Hang Thi Dao; G. Andrew C. Beattie; Amy Y. Rossman; Lester W. Burgess; Paul Holford (Mycological Progress, 2016)

Systematics and biology of two species of Microcera associated with armoured scales on citrus in Australia - Hang Thi Dao; G. Andrew C. Beattie; Amy Y. Rossman; Lester W. Burgess; Paul Holford (Mycological Progress, 2015)

Predicting the likely response of data‐poor ecosystems to climate change using space‐for‐time substitution across domains - Rebecca E. Lester; Paul G. Close; Jan L. Barton; Adam J. Pope; Stuart C. Brown (Global Change Biology, 2014)
Predicting ecological response to climate change is often limited by a lack of relevant local data from which directly applicable mechanistic models can be developed. This limits predictions to qualitative assessments or simplistic rules of thumb in data‐poor regions, making management of the relevant systems difficult. We demonstrate a method for developing quantitative predictions of ecological response in data‐poor ecosystems based on a space‐for‐time substitution, using distant, well‐studied systems across an inherent climatic gradient to predict ecological response. Changes in biophysical data across the spatial gradient are used to generate quantitative hypotheses of temporal ecological responses that are then tested in a target region. Transferability of predictions among distant locations, the novel outcome of this method, is demonstrated via simple quantitative relationships that identify direct and indirect impacts of climate change on physical, chemical and ecological variables using commonly available data sources. Based on a limited subset of data, these relationships were demonstrably plausible in similar yet distant (>2000 km) ecosystems. Quantitative forecasts of ecological change based on climate‐ecosystem relationships from distant regions provides a basis for research planning and informed management decisions, especially in the many ecosystems for which there are few data. This application of gradient studies across domains – to investigate ecological response to climate change – allows for the quantification of effects on potentially numerous, interacting and complex ecosystem components and how they may vary, especially over long time periods (e.g. decades). These quantitative and integrated long‐term predictions will be of significant value to natural resource practitioners attempting to manage data‐poor ecosystems to prevent or limit the loss of ecological value. The method is likely to be applicable to many ecosystem types, providing a robust scientific basis for estimating likely impacts of future climate change in ecosystems where no such method currently exists.

Genome-wide association study of subtype-specific epithelial ovarian cancer risk alleles using pooled DNA - Madalene A. Earp; Linda E. Kelemen; Anthony M. Magliocco; Kenneth D. Swenerton; Georgia Chenevix-Trench; Yi Lu; Alexander Hein; Arif B. Ekici; Matthias W. Beckmann; Peter A. Fasching; Diether Lambrechts; Evelyn Despierre; et al. (Human Genetics, 2014)

Cross-infectivity and genetic variation of Phytophthora capsici isolates from chilli and black pepper in Vietnam - Nguyen V. Truong; Lester W. Burgess; Edward C. Y. Liew (Australasian Plant Pathology, 2012)

Nicotine is a Selective Pharmacological Chaperone of Acetylcholine Receptor Number and Stoichiometry. Implications for Drug Discovery - Henry A. Lester; Cheng Xiao; Rahul Srinivasan; Cagdas D. Son; Julie Miwa; Rigo Pantoja; Matthew R. Banghart; Dennis A. Dougherty; Alison M. Goate; Jen C. Wang (The AAPS Journal, 2009)

Antennal Electrophysiological Responses of Three Parasitic Wasps to Caterpillar-Induced Volatiles from Maize (Zea mays mays), Cotton (Gossypium herbaceum), and Cowpea (Vigna unguiculata) - Sandrine Gouinguené; John A. Pickett; Lester J. Wadhams; Michael A. Birkett; Ted C. J. Turlings (Journal of Chemical Ecology, 2005)

Improving the expression of mini-proinsulin in Pichia pastoris - José M. País-Chanfrau; Yuneski García; Lisandra Licor; Vladimir Besada; Lila Castellanos-Serra; Cecilia I. Cabello; Lester Hernández; Manuel Mansur; Liuba Plana; Abdel Hidalgo; Yanet Támbara; María del C. Abrahantes-Pérez; et al. (Biotechnology Letters, 2004)

A genome-wide search for allergic response (atopy) genes in three ethnic groups: Collaborative Study on the Genetics of Asthma - Malcolm N. Blumenthal; Carl D. Langefeld; Terri H. Beaty; Eugene R. Bleecker; Carole Ober; Lucille Lester; Ethan Lange; Kathleen C. Barnes; Raoul Wolf; Richard A. King; Julian Solway; William Oetting; et al. (Human Genetics, 2004)

Transgenic Tobacco and Apple Plants Expressing Biotin-binding Proteins are Resistant to two Cosmopolitan Insect Pests, Potato Tuber Moth and Lightbrown Apple Moth, Respectively - Ngaire P. Markwick; Lisa C. Docherty; Margaret M. Phung; Melissa T. Lester; Colleen Murray; Jia-Long Yao; Deepali S. Mitra; Daniel Cohen; Lesley L. Beuning; Sumathi Kutty-Amma; John T. Christeller (Transgenic Research, 2003)

Stock discrimination and movements of narrow‐barred Spanish mackerel across northern Australia as indicated by parasites - B. R. Moore; R. C. Buckworth; H. Moss; R. J. G. Lester (Journal of Fish Biology, 2003)
The parasite fauna of Spanish mackerel Scomberomorus commerson from 10 sites across northern Australia and one site in Indonesia, was examined to evaluate the degree of movement and subsequent stock structure of the fish. Kupang fish (Indonesia) had very few Terranova spp., Grillotia branchi , Otobothrium cysticum or Pterobothrium sp. compared to Australian fish, indicating that no Australian fish enter the Kupang fishery. Univariate and discriminant function analysis of four ‘temporary’ parasite species, the copepod Pseudocycnoides armatus and the monogeneans Gotocotyla bivaginalis , Pricea multae and Pseudothoracocotyla ovalis , demonstrated little similarity between areas of northern Australia, indicating minimal short‐term exchange between neighbouring groups of S. commerson . Analyses of five ‘permanent’ parasite species, the larval helminths G. branchi , O. cysticum , Pterobothrium sp., Callitetrarhynchus gracilis and Paranybelinia balli , also revealed large differences between areas thus indicating long‐term separation. There are at least six parasitological stocks across northern Australia: Fog Bay/Bathurst Island, Cape Wessel, Groote/Sir Edward Pellew, Mornington Island, Weipa, and the Torres Strait. The occurrence of a few irregular fish in the samples suggested that up to 5% of fish moved between stocks during their lifetime. The similarity of within‐school variability to that between schools showed that the fish do not form long‐term school associations.

Interaction of Formaldehyde with Soil Humic Substances: Separation by GFC and Characterization by 1 H-NMR Spectroscopy - C. M. Cooke; N. J. Bailey; G. Shaw; J. N. Lester; C. D. Collins (Bulletin of Environmental Contamination and Toxicology, 2003)

Near-infrared spectral imaging for quality assurance of pharmaceutical products: Analysis of tablets to assess powder blend homogeneity - Robbe C. Lyon; David S. Lester; E. Neil Lewis; Eunah Lee; Lawrence X. Yu; Everett H. Jefferson; Ajaz S. Hussain (AAPS PharmSciTech, 2002)

Influence of Leaching Protocol Regimes on Losses of Wood Preservative Biocides - J. A. Hingston; A. Bacon; J. Moore; C. D. Collins; R. J. Murphy; J. N. Lester (Bulletin of Environmental Contamination and Toxicology, 2002)

Influence of Leaching Protocol Regimes on Losses of Wood Preservative Biocides - J. A. Hingston; A. Bacon; J. Moore; C. D. Collins; R. J. Murphy; J. N. Lester (Bulletin of Environmental Contamination and Toxicology, 2002)

Movement and stock structure of narrow‐barred Spanish mackerel as indicated by parasites - R. J. G. Lester; C. Thompson; H. Moss; S. C. Barker (Journal of Fish Biology, 2001)
Data from permanent parasites (juvenile trypanorhynchs and anisakids) indicated that Spanish mackerel Scomberomorus commerson from four sites on the west coast of Australia, Abrolhos. Shark Bay, Exmouth and Onslow, intermingled and were probably all drawn from the same stock. Fish from Broome, Kupang (Indonesia), Groote Eylandt‐Torres Strait and the east coast of Australia had distinct faunas of permanent parasites and probably each belonged to a different stock. There was evidence of movement of fish between Broome and the west coast. Abundances of temporary parasites (gill copepods and monogeneans) suggested that males and females on the west coast migrated separately because in several cases the parasite fauna of one sex was more similar to that offish in an adjacent area than to the opposite sex in the same area.

Feed-Forward Regulation of Gibberellin Deactivation in Pea - Robert C. Elliott; John J. Ross; Jennifer J. Smith; Diane R. Lester; James B. Reid (Journal of Plant Growth Regulation, 2001)

Estimation of genetic parameters in a recurrent selection program in Apple - Nnadozie C. Oraguzie; Madeleine E. Hofstee; Lester R. Brewer; Craig Howard (Euphytica, 2001)

AFLP analysis of genetic relationships in the tribe Datureae (Solanaceae) - E. S. Mace; C. G. Gebhardt; R. N. Lester (Theoretical and Applied Genetics, 1999)

AFLP analysis of genetic relationships among the cultivated eggplant, Solanummelongena L., and wild relatives (Solanaceae) - E. S. Mace; R. N. Lester; C. G. Gebhardt (Theoretical and Applied Genetics, 1999)

Mercury Contamination of the EEL (Anguilla Anguilla) and Roach (Rutilus Rutilus) in East Anglia, UK - Sion C. Edwards; Cecilia L. MacLeod; John N. Lester* (Environmental Monitoring and Assessment, 1999)

Mercuty in Precipitation and Its Relation to Bioaccumulation in Fish: A Literature Review - S. G. Downs; C. L. MacLeod; J. N. Lester (Water, Air, & Soil Pollution, 1998)

The Bioavailability of Copper and Mercury to the Common Nettle (Urtica Dioica) and the Earthworm Eisenia Fetida from Contaminated Dredge Spoil - Sion C. Edwards; Cecilia L. MacLeod; John N. Lester (Water, Air, & Soil Pollution, 1998)

Clean Recycling of Lead‐Acid Batteries for Electric Vehicles: A Reply to Socolow and Thomas - Lester B. Lave; Chris T. Hendrickson; Francis C. McMichael (Journal of Industrial Ecology, 1997)
Summary This article is stimulated by the analysis of Socolow and Thomas in the first issue of this journal. Our work showed that a lead‐acid battery‐powered electric vehicle (Ev) would result in more lead being discharged into the environment than a comparable car burning leaded gasoline. Five hundred thousand EVs would lead to a 20% increase in lead use in the United States, and presumably a comparable 20% increase in lead discharges. The Socolow‐Thomas analysis asserts: (I) choosing not to pursue technology that uses toxic materials will unduly constrain the research and development (R&D) in advanced vehicles and limit the options likely to emerge from that research; (2) we do not do a full risk assessment of the lead discharges from lead smelting, battery making and recycling; and (3) in response to regulation the industry might devise a “clean recycling” system. We doubt the wisdom of increasing R&D on lead batteries because introducing large quantities of lead into cars will pose health risks. The possibility of clean recycling in the future is not an adequate basis for mandating EVs. Proponents of EVs should prove there is no harm to the environment Regulators should not require EVs until there is a reasonable showing of environmental benefit and that the requirement is cost‐effective in reducing ozone.

Mapping the bovine factor H gene to Chromosome 16 by SSCP analysis - J. L. Williams; D. H. Lester; V. M. Teres; W. Barendse; R. B. Sim; C. J. Soames (Mammalian Genome, 1997)

Isolation of parafluorophenylalanine-resistant mutants from HeLa cell cultures - Lester K. C. Yim; W. Dorsey Stuart (Biochemical Genetics, 1983)

Coronavirus-like particles in nonhuman primate feces - G. C. Smith; T. L. Lester; R. L. Heberling; S. S. Kalter (Archives of Virology, 1982)